Complications of Ilizarov method treatment for infected nonunion femoral shaft fracture - Hossain, M. Zakir; Chandra Sarker, Manash; Alam, M. Jahangir; Ferdousi, Naima; Mollah, M. Abdul Gani; Huda Setu, Nazmul; Manzur, Raquib Mohammad; Bhowmik, Devolina (International Journal of Research in Orthopaedics, 2024)
Background: Infected non-union of the femur is complicated by the involvement of soft tissue and bone, long-term resistant multi-bacterial infection, limb length discrepancy, deformities, joint stiffness, and multiple draining sinuses, and poses a challenge for orthopedic surgeons. This study aimed to analyze the complications of Ilizarov method treatment for infected non-union femoral shaft fracture. Methods: This prospective observational study was conducted at the national institute of traumatology and orthopedic rehabilitation (NITOR), Dhaka, Bangladesh, from May 2018 to August 2020. A total of 20 patients were selected as study subjects by purposive sampling technique. All data were collected using a pre-formed questionnaire. Data were processed and analyzed using computer software program SPSS version 22.0. Result: The mean bone gap created during the operation was 2.7±1.7 cm of them, in 12 (60%) patients, it was 0 to 2 cm, and in 8 (40%) patients it was more than 2 cm. The mean time needed for radiological union was 7.85±2.1 months ranging from 5 months to 11 months. In 10 (50%) patients, union was achieved within 4 to 7 months, and in 10 (50%) patients it was 8 to 11 months. Regarding limb length discrepancy, in 5 (25%) cases there was no limb length discrepancy (LLD). Twelve patients had 1 cm to 2.4 cm LLD and 3 (15%) patients had ≥2.5 cm LLD. The mean LLD was 1.2±0.9 cm. Regarding complications, in 10 (50%) cases, there was no complication and 10 (50%) patients had complications. The complications were pin tract infection in 7 (35%) patients and wire loosening in 3 (15%) patients. Conclusions: The study concludes that while the Ilizarov ring fixator proves to be a dependable and successful method for stabilizing, correcting length discrepancies, and eliminating infections, it is not without its share of complications. The findings of this research indicate a 50% complication rate among the patients undergoing this treatment.